2017
DOI: 10.3390/su9050724
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land-Cover/Land-Use Change and Landscape Patterns in the Two National Nature Reserves of Ebinur Lake Watershed, Xinjiang, China

Abstract: Abstract:Land-cover and land-use change (LCLUC) alters landscape patterns and affects regional ecosystems. The objective of this study was to examine LCLUC and landscape patterns in Ebinur Lake Wetland National Nature Reserve (ELWNNR) and Ganjia Lake Haloxylon Forest National Nature Reserve (GLHFNNR), two biodiversity-rich national nature reserves in the Ebinur Lake Watershed (ELW), Xinjiang, China. Landsat satellite images from 1972, 1998, 2007 and 2013 were used to calculate the dynamics of a land-cover and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 46 publications
0
35
0
1
Order By: Relevance
“…The study on Wang Thong watershed in Northern Thailand showed that the watershed has experienced significant land use change due to the change in its agricultural policy promoting rubber production for export markets [43]. Similar observations have recently been reported by Zhang et al [44] where the Chinese government promoted cotton farming resulting in changes in land use particularly expansion and intensification of cotton farming in the expense of the wetlands of Ebinur Lake Watershed, Western China. This is also the case in Kilombero valley floodplain, whereby various land use related policies implemented by the Tanzanian government have influence land use change and wetland conversion.…”
Section: Policy and Institutional Framework Factormentioning
confidence: 54%
See 2 more Smart Citations
“…The study on Wang Thong watershed in Northern Thailand showed that the watershed has experienced significant land use change due to the change in its agricultural policy promoting rubber production for export markets [43]. Similar observations have recently been reported by Zhang et al [44] where the Chinese government promoted cotton farming resulting in changes in land use particularly expansion and intensification of cotton farming in the expense of the wetlands of Ebinur Lake Watershed, Western China. This is also the case in Kilombero valley floodplain, whereby various land use related policies implemented by the Tanzanian government have influence land use change and wetland conversion.…”
Section: Policy and Institutional Framework Factormentioning
confidence: 54%
“…It is among the major driving factors of land use change processes in various ecosystems that influence environmental degradation at the local, regional and global scale. Wetland ecosystems are particularly sensitive to climate change and variability as its affects hydrology, biogeochemical processes, plant communities and ecosystem function [44]. The temperature change in Ebinur Lake Watershed (ELW), Western China leads to high evaporation affecting the hydrology of the wetlands, although there was high precipitation time to time in ELW, the precipitation could not surpass the higher evaporation rate [44].…”
Section: Climate Change and Variability Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The Ebinur Lake Basin is located in the northwest arid area in Xinjiang Uygur Autonomous Region, and it ranges from 44°54′ to 45°08′ N and 82°35′ to 83°10′ E ( Figure 1 ) [ 22 ]. Ebinur Lake is a national desert natural ecological protection area and the lowest depression and saltwater-collecting centre in western of Junggar Basin [ 23 ]. The Bortala River, Jing River, and Kuitun River run into Ebinur Lake from the west, south, and east, respectively, and are the main sources of lake water [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Land use changes could be caused by alternations in hydrological conditions, but they can also cause changes in the water cycle. Moreover these changes are very important at scales both regional (Zhang et al 2017;Fu et al 2013; Wright and Wimberly 2013) and global (Sterling et al 2013). That is why the interdependencies between the anthropogenic impact, water management and land cover changes in wetland areas are widely studied.…”
Section: Introductionmentioning
confidence: 99%